Pengaruh Penerapan Metode Diskusi oleh guru PAK terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 1 Siatas Barita Tahun Pembelajaran 2022/2023 - Christina Dhea Simamora (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The aim of this research is to determine the effect of applying the Discussion Method by PAK teachers on the Learning Motivation of Class VIII Students at SMP Negeri 1 Siatas Barita T.P 2022/2023. The method used in this research is a quantitative research method. The population is all 146 students of class VIII of SMP Negeri 1 Siatas Barita who are Christians. The sample was taken from 30% of 146 class VIII students at SMP Negeri 1 Siatas Barita, namely 43 people. Data was collected using a positive closed questionnaire with 32 items. The results of data analysis show that there is a positive and significant influence of the application of the Discussion Method by PAK teachers on the Learning Motivation of class VIII students at SMP Negeri 1 Siatas Barita T.P 2022/2023 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.462 > rtable (a=0.05,n=43) = 0.301, thus it is known that there is a positive relationship between variable n-2=41)=2.021, thus there is a significant relationship between variable X and variable Y. c) Test the effect of regression determination (r2) = 21.34%. 2) Influence test: Regression equation test, obtained regression equation Ŷ=16.30+0.28X. Thus Ha is accepted and H0 is rejected. This research concludes that there is a positive and significant influence of the application of the Discussion Method by PAK teachers on the Learning Motivation of Class VIII Students at SMP Negeri 1 Siatas Barita T.P 2022/2023 amounting to 21.34%.